Оценка отдаленных последствий острых тяжелых отравлений нейротоксикантами - Батоцыренова, Екатерина Геннадьевна; Кострова, Таисия Александровна; Щепеткова, Кристина Михайловна; Золотоверхая, Екатерина Андреевна; Степанов, Сергей Васильевич; Кашуро, Вадим Анатольевич (Медицина: теория и практика, 2020)